Evaluasi Usability Website JOOX dengan Metode Website Analysis and Measurement Inventory (WAMMI) - Sudarto; Sophya Hadini Marpaung; Mirza Ilhami (SNASTIKOM, 2022)
Website is one of the important components that can be used to support the marketing activities of products and services of an organization or company. However, in developing a website there are many aspects that need to be considered, one of which is the usability aspect. The purpose of this project is to evaluate the usability of the Joox Website. Research on this project uses the Website Analysis and Measurement Inventory (WAMMI) method to evaluate the website. The components of WAMMI are Attractiveness (Attractiveness), Controllability (Control), Efficiency (Efficiency), Helpfulness (Useful) and Learnability (Easy to learn). The results of this project indicate that based on the WAMMI questionnaire, the Joox website has a good usability level.